Long Road to Harpers Ferry The Rise of the First American Left - Lause, Mark A. (Pluto Press, 2018)
This is the first comprehensive history of pre-Civil War American radicalism, mapping the journeys of the land reformers, Jacksonian radicals and militant abolitionists on the long road to the failed slave revolt of Harpers Ferry in 1859. This book contains new and fascinating insights into the cast of characters who created a homegrown American socialist movement through the nineteenth century - from Thomas Paine's revolution to Robert Owen's utopianism, from James Macune Smith, the black founder of organised socialism in the US, to Susan B. Anthony, the often overlooked women's rights activist. It also considers the persistent pre-capitalist model of the Native American. Long Road to Harpers Ferry captures the spirit of the times, showing how class solidarity and consciousness became more important to a generation of workers than notions of American citizenship. This is a story that's been hidden from official histories, which must be remembered if we are to harness the latent power of socialism in the United States today.